2009
DOI: 10.1002/ijc.24160
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B inhibits growth of head and neck squamous cell carcinoma in vitro and in vivovia cyclooxygenase‐2 and apoptotic pathways

Abstract: Overexpression of cyclooxygenase‐2 (COX‐2) in oral mucosa has been associated with increased risk of head and neck squamous cell carcinoma (HNSCC). Celecoxib is a nonsteroidal anti‐inflammatory drug, which inhibits COX‐2 but not COX‐1. This selective COX‐2 inhibitor holds promise as a cancer preventive agent. Concerns about cardiotoxicity of celecoxib, limits its use in long‐term chemoprevention and therapy. Salvianolic acid B (Sal‐B) is a leading bioactive component of Salvia miltiorrhiza Bge, which is used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 38 publications
4
70
0
2
Order By: Relevance
“…Salvianolic acid B also shows promise as a cyclooxygenase 2-targeted anticancer agent for the prevention and treatment of head and neck squamous-cell carcinoma (Hao et al, 2009).…”
Section: Rosmarinic Acid Derivativesmentioning
confidence: 99%
“…Salvianolic acid B also shows promise as a cyclooxygenase 2-targeted anticancer agent for the prevention and treatment of head and neck squamous-cell carcinoma (Hao et al, 2009).…”
Section: Rosmarinic Acid Derivativesmentioning
confidence: 99%
“…Mounting studies have reported that Sal-B is capable of preventing the development of cancer; and the possible antiinflammatory mechanisms of Sal-B involve modulating cytokines, Cyclooxygenase-2/prostaglandin E2 (COX-2/PGE-2) pathway [24, 25, 29], NF- κ B [3032], TNF- α [3335] and MMPs [36–38]. Numbers of clinical experiences indicate its effectiveness and safety in contrast to the disadvantages of nonsteroidal antiinflammatory drugs (NSAIDs).…”
Section: Antiinflammatory Activitiesmentioning
confidence: 99%
“…Salvianolic acid는 수용성으 로 salvianolic acid A (SAA)와 salvianolic acid B (SAB)로 구분되며 간 보호효능 2) , 신경손상 보호효능 3) , 항암 효능 4) 등이 있는 것으로 보고되어 있다. SAA와 SAB 모두 높은 항 산화 작용이 있는 것으로 보고되고 있으며 5) , 특히 SAB는 혈관내피세포, 혈관 평활근세포 및 심근세포에 대한 연구들 을 통해 심혈관 보호(cardiovascular protection)와 심장손 상 보호(cardioprotection)의 효능이 있다고 하였다 6) .…”
Section: 서 론unclassified